Characterization of binding, functional activity, and contractile responses of the selective 5‐HT(1F) receptor agonist lasmiditan - Rubio‐Beltrán, Eloísa (Br J Pharmacol, 2019)
BACKGROUND AND PURPOSE: Triptans are 5‐HT(1B/1D) receptor agonists (that also display 5‐HT(1F) receptor affinity) with antimigraine action, contraindicated in patients with coronary artery disease due to their vasoconstrictor properties. Conversely, lasmiditan was developed as an antimigraine 5‐HT(1F) receptor agonist. To assess the selectivity and cardiovascular effects of lasmiditan, we investigated the binding, functional activity, and in vitro/in vivo vascular effects of lasmiditan and compared it to sumatriptan. EXPERIMENTAL APPROACH: Binding and second messenger activity assays of lasmiditan and other serotoninergic agonists were performed for human 5‐HT(1A), 5‐HT(1B), 5‐HT(1D), 5‐ht(1E), 5‐HT(1F), 5‐HT(2A), 5‐HT(2B), and 5‐HT(7) receptors, and the results were correlated with their potency to constrict isolated human coronary arteries (HCAs). Furthermore, concentration–response curves to lasmiditan and sumatriptan were performed in proximal and distal HCA, internal mammary, and middle meningeal arteries. Finally, anaesthetized female beagle dogs received i.v. infusions of lasmiditan or sumatriptan in escalating cumulative doses, and carotid and coronary artery diameters were measured. KEY RESULTS: Lasmiditan showed high selectivity for 5‐HT(1F) receptors. Moreover, the functional potency of the analysed compounds to inhibit cAMP increase through 5‐HT(1B) receptor activation positively correlated with their potency to contract HCA. In isolated human arteries, sumatriptan, but not lasmiditan, induced contractions. Likewise, in vivo, sumatriptan decreased coronary and carotid artery diameters at clinically relevant doses, while lasmiditan was devoid of vasoconstrictor activity at all doses tested. CONCLUSIONS AND IMPLICATIONS: Lasmiditan is a selective 5‐HT(1F) receptor agonist devoid of vasoconstrictor activity. This may represent a cardiovascular safety advantage when compared to the triptans.